Carta de Santos G. Ramírez a Roberto H. Todd - Ramírez, Santos; Todd, Roberto H. (My University, 1924)
Carta relacionado con la designación de, Sub-Auditor de Puerto Rico
Keywords: Puerto Rico--Politics and government.; Puerto Rico--Política y gobierno.; Mc Cown, F.D.; Tormes, Leopoldo; Colón, Felipe; Varela, Manuel; Cantellops, Trujillo; Santiago, Juan